Effects and Adherence of Mirror Therapy in People with Chronic Upper Limb Hemiparesis: A Preliminary Study. (14th November 2012) - Kuys, Suzanne S.; Edwards, Tara; Morris, Norman R.
Abstract : Mirror therapy is a promising therapy with some benefit for motor recovery in people with chronic hemiparesis. However, there has been little investigation on the effect on upper limb sensory impairments, activity limitations, and participation restrictions. A within-subject, repeated-measures study with 12 people with chronic hemiparesis was conducted. Participants underwent a thirty minute sensorimotor mirror therapy home-based exercise program, conducted three times per week for six weeks. Compliance with the program and the effect on sensory outcomes were determined. Light touch threshold and proprioceptive error, upper limb activity limitations, and participation restrictions were measured at baseline (Week 0), immediately after (Week 6), and six weeks (Week 12) following the intervention. Compliance with the program was fair, 66% of supervised and 62% of unsupervised sessions were completed. The paretic hand performed worse compared to nonparetic hand at baseline with no difference in sensory measures demonstrated over time. Activity limitations and participation restrictions improved by Week 12 (P < 0.05 ). This sensorimotor mirror therapy home-based exercise program showed small improvements in light touch threshold and proprioception that appear to be functionally important for this group of people with chronic hemiparesis. Mirror therapy may be a useful tool for clinicians particularly for patient independent use.